Who is paying all these fees? An empirical analysis of bank account and credit card fees - Oz Shy; Joanna Stavins (Federal Reserve Bank of Boston, 2022)
Banks impose a variety of account fees, and credit card issuers impose a variety of fees related to card usage. Using detailed data from a 2021 representative diary survey of US consumers, we investigate whether lower-income consumers and Black consumers are more likely to pay bank account or credit card fees, and how payment behavior varies depending on paying such fees. We find that the probability of paying several types of bank account and credit card fees is correlated with consumers' demographic attributes and payment behavior. The percentage of Black consumers who pay overdraft or low-balance fees on their bank accounts or pay late fees or cash-advance fees on their credit cards is higher than the percentage of White consumers who pay those fees. We find that lower-income consumers were significantly more likely to pay overdraft fees, and Black consumers were significantly more likely to pay any bank account fee when we hold income and account balances constant in the regressions. However, when controlling for income, we find that the race effect was smaller than in the summary statistics.
Keywords: G21; G5; D14; 330; Bank account fees; credit card fees; fees by demographics; payment choice